PENERAPAN E-LEARNING BERBASIS WEB BLOG PADA PEMBELAJARAN BOLA BASKET DI SMP NEGERI 9 LUBUKLINGGAU - Muhammad Fariz Alfarozi Gumay; Dodik Mulyono; Wawan Syafutra (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
ABSTRACT This study aims to determine the completeness of the learning outcomes of eighth grade students of SMP Negeri 9 Lubuklinggau after the application of Web Blog- based E Learning learning media significantly. The research method used is quasi- experimental. Data collection techniques in research using tests. The design in this study used a design pattern of Pre-test and Post-test one group design because this design did not use a control class. Based on the results of the study, it can be concluded that after the application of Web-based E-Learning blogs on the football learning outcomes of VIII Junior high school of SMP Negeri 9 Lubuklinggau, it was significantly completed. The average student learning outcomes of the experimental class were 80.38, after being analyzed using the formula (z test) it showed that the value was > (6.35 > 1.64) so it could be concluded that H0 was rejected and Ha was accepted. So it can be concluded that the average learning outcomes of Class XI students of SMK Negeri 2 Tugumulyo after implementing Web-based E-Learning blogs are more than or equal to 75. ( : ????0 ≥ 75). Keywords: E-Learning, Learning outcomes, Webblog.